Analysis of tool-particle interactions during cutting process of metal matrix composites. Issue 1 (January 2016) - Ghandehariun, A.; Kishawy, H.; Umer, U.; Hussein, H.
Abstract Metal matrix composites (MMCs) have become common materials that are employed in different industrial applications due to their outstanding strength and wear resistance. However, machining MMCs is considered to be a challenging process. This paper presents a micro-mechanical finite element analysis developed for simulation of MMC machining. Unlike the previously developed FE models, this model simulates the behavior of all main components that distinguish the MMC, namely the matrix, particles, and the particle-matrix interface, during the process. As a result, various aspects of the process, such as debonding and fracture in the particles and different scenarios of tool-particle interactions can be studied using the proposed model. The predicted forces were compared to the measured ones and used to verify the presented model. The developed model is successful in providing a broad understanding of MMC machining process.